Comparison of Videostroboscopy and High-speed Videoendoscopy in Evaluation of Supraglottic Phonation. (October 2016) - Zacharias, Stephanie R. C.; Myer, Charles M.; Meinzen-Derr, Jareen; Kelchner, Lisa; Deliyski, Dimitar D.; de Alarcón, Alessandro
Objectives: To compare clinicians' ratings of videolaryngoscopy (VLS) and high-speed videoendoscopy (HSV) and assess confidence of ratings with VLS and HSV in patients with supraglottic phonation. Methods: The VLS and HSV video samples were taken from 11 adolescents post airway reconstruction who use supraglottic tissues for voice. The 22 recordings were randomized and presented to 4 clinicians: 2 speech-language pathologists and 2 pediatric otolaryngologists. Additionally, a 5-point Likert scale was used to rate level of confidence of ratings. Results: Clinicians were more likely to rate regularity on HSV versus VLS videos ( P = .003). Presence of mucosal wave was rated similarly on both imaging modalities; however, HSV was more likely to identify location ( P = .002). Supraglottic phase symmetry ( P = .014) and number of vibratory tissues used for phonation were rated more often with HSV versus VLS. Clinicians were more confident with HSV ratings compared to VLS ratings for determining vibration source, vibration pattern, and ability to make treatment decisions ( P < .0001). Conclusions: The HSV improves the ability to rate tissue vibratory characteristics when compared with VLS in children with supraglottic phonation. This information may allow better understanding of the underlying mechanisms of voice production in these individuals, leading to improved therapeutic and surgical recommendations.